NATION-WIDE SURVEY ON THE USE OF THROMBOPOIETIN RECEPTOR AGONISTS (TPO-RA) FOR THE MANAGEMENT OF IMMUNE THROMBOCYTOPENIA IN CURRENT CLINICAL PRACTICE IN ITALY - Francesco Rodeghiero; Mariasanta Napolitano (Mediterranean Journal of Hematology and Infectious Diseases)
Background: Two thrombopoietin receptor agonists (TPO-RA), romiplostim and eltrombopag, are currently widely adopted as second-line ITP therapy even in absence of robust evidence on their comparative advantages over rituximab or splenectomy or their preferential use in some specific clinical contexts.